G1/ELE Functions in the Development of Rice Lemmas in addition to Determining Identities of Empty Glumes - Mengjia Liu (Frontiers in Plant Science, 2016)
Rice empty glumes, also named sterile lemmas or rudimentary lemmas according to different interpretations, are distinct from lemmas in morphology and cellular pattern. Consistently, the molecular mechanism to control the development of lemmas is different from that of empty glumes. Rice LEAFY HULL STERILE1(OsLHS1) and DROOPING LEAF(DL) regulate the cellular pattern and the number of vascular bundles of lemmas respectively, while LONG STERILE LEMMA1 (G1)/ELONGATED EMPTY GLUME (ELE) and PANICLE PHYTOMER2 (PAP2)/OsMADS34 determine identities of empty glumes. Though some progress has been made, identities of empty glumes remain unclear, and genetic interactions between lemma genes and glume genes have been rarely elucidated. In this research, a new G1/ELE mutant g1-6 was identified and the phenotype was analyzed. Similar to previously reported mutant lines of G1/ELE, empty glumes of g1-6 plants transform into lemma-like organs. Furthermore, Phenotypes of single and double mutant plants suggest that, in addition to their previously described gene-specific functions, G1/ELE and OsLHS1 play redundant roles in controlling vascular bundle number, cell volume, and cell layer number of empty glumes and lemmas. Meanwhile, expression patterns of G1/ELE in osmads1-z flowers and OsLHS1 in g1-6 flowers indicate they do not regulate each other at the level of transcription. Finally, down-regulation of the empty glume gene OsMADS34/PAP2 and ectopic expression of the lemma gene DL, in the g1-6 plants provide further evidence that empty glumes are sterile lemmas. Generally, our findings provided valuable information for better understanding functions of G1 and OsLHS1 in flower development and identities of empty glumes.